Pengaruh Kualitas Informasi Akuntansi Dan Corporate Governance terhadap Peringkat Sukuk Korporasi Indonesia - Nurhanifah, Afifa; Violita, Evony Silvino (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
This research aims to examine the association accounting information quality (accrual quality and cash flow management) and corporate governance to affects corporation sukuk rating. Using sukuk rating as dependent variable, ordered logit model selected to test research variable. Research periods start from year 2010 – 2015, with 92 observations sukuk rating in Indonesia. This research finds that accrual quality, cash flow management and corporate governance, positively associated with sukuk rating.